A division-of-labor mode contributes to the cardioprotective potential of mesenchymal stem/stromal cells in heart failure post myocardial infarction - Wang, Xicheng; Yang, Chao; Ma, Xiaoxue; Li, Xiuhua; Qi, Yiyao; Bai, Zhihui; Xu, Ying; Ma, Keming; Luo, Yi; Song, Jiyang; Jia, Wenwen; He, Zhiying; et al. (Frontiers in Immunology, 2024)
Treatment of heart failure post myocardial infarction (post-MI HF) with mesenchymal stem/stromal cells (MSCs) holds great promise. Nevertheless, 2-dimensional (2D) GMP-grade MSCs from different labs and donor sources have different therapeutic efficacy and still in a low yield. Therefore, it is crucial to increase the production and find novel ways to assess the therapeutic efficacy of MSCs.hUC-MSCs were cultured in 3-dimensional (3D) expansion system for obtaining enough cells for clinical use, named as 3D MSCs. A post-MI HF mouse model was employed to conduct in vivo and in vitro experiments. Single-cell and bulk RNA-seq analyses were performed on 3D MSCs. A total of 125 combination algorithms were leveraged to screen for core ligand genes. Shinyapp and shinycell workflows were used for deploying web-server.3D GMP-grade MSCs can significantly and stably reduce the extent of post-MI HF.To understand the stable potential cardioprotective mechanism, scRNA-seq revealed the heterogeneity and division-of-labor mode of 3D MSCs at the cellular level. Specifically, scissor phenotypic analysis identified a reported wound-healing CD142 + MSCs subpopulation that is also associated with cardiac protection ability and CD142 -MSCs that is in proliferative state, contributing to the cardioprotective function and self-renewal, respectively. Differential expression analysis was conducted on CD142 + MSCs and CD142 -MSCs and the differentially expressed ligand-related model was achieved by employing 125 combination algorithms. The present study developed a machine learning predictive model based on 13 ligands.Further analysis using CellChat demonstrated that CD142 + MSCs have a stronger secretion capacity compared to CD142 -MSCs and Flow cytometry sorting of the CD142 + MSCs and qRT-PCR validation confirmed the significant upregulation of these 13 ligand factors in CD142 + MSCs. Clinical GMP-grade 3D MSCs could serve as a stable cardioprotective cell product.Using scissor analysis on scRNA-seq data, we have clarified the potential functional and proliferative subpopulation, which cooperatively contributed to self-renewal and functional maintenance for 3D MSCs, named as "division of labor" mode of MSCs.Moreover, a ligand model was robustly developed for predicting the secretory efficacy of MSCs. A user-friendly web-server and a predictive model were constructed and available (https://wangxc.shinyapps.io/3D_MSCs/).